Analisis Dampak Pengangguran Terhadap Tingkat Kemiskinan di Kepulauan Riau - Haamidah, Szahara Nur; Salbilah, Salwa Izmi; Desmawan, Deris; Andini, Fitri Yulia; Fachriza, Salma Yuri; Saputra, Alfito Yuniawan (Universitas Labuhanbatu, 2023)
Unemployment and poverty rates are two dimensions that are related or interrelated. The unemployment rate is a measure for calculating or knowing the poverty rate. The survey was conductedÂ due toÂ precarious unemployment in Riau andÂ low unemployment in Keplau. This study aims to analyze data on the impact on unemployment and poverty in Keplauan his Riau province. The research method used is quantitative research. The analytical method used in this study is the secondary data test. This study shows (1) the impact of poverty rate on unemployment rate in Keplauan-Liau Province; (2) There are other dimensions that also affect levels of unemployment and poverty.